2021
DOI: 10.51329/mehdioptometry120
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical treatment of primary open angle glaucoma

Abstract: Background: Glaucoma is a progressive, irreversible optic neuropathy that results in serious vision loss and blindness. This review aimed to summarize key concepts of primary open angle glaucoma (POAG) pharmaceutical treatment trials over the last decade. Methods: We searched PubMed/MEDLINE and clinicaltrials.gov from January 1, 2010, to August 31, 2020, using the key words “POAG” and “Ocular topical therapeutics”. This search yielded 77 and 120 papers, respectively. Results: Thirty-three records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…It has been predicted that in 2050, 6.3 million people will have a diagnosis of glaucoma [ 60 ] . Clinical trials on pharmaceutical treatment of primary open-angle glaucoma have found that medical treatment is effective, safe, and positively affects quality of life [ 65 , 66 ] . Glaucoma interventions have been summarized in a recently published review article.…”
Section: Discussionmentioning
confidence: 99%
“…It has been predicted that in 2050, 6.3 million people will have a diagnosis of glaucoma [ 60 ] . Clinical trials on pharmaceutical treatment of primary open-angle glaucoma have found that medical treatment is effective, safe, and positively affects quality of life [ 65 , 66 ] . Glaucoma interventions have been summarized in a recently published review article.…”
Section: Discussionmentioning
confidence: 99%
“…I read with great interest the article by Dr. Mashael Al-Namaeh, entitled "Pharmaceutical treatment of primary open-angle glaucoma. " In this article, the author concentrated on an interesting and remarkable area in POAG treatment [1]; however, a few issues may be worth considering regarding race and its role in glaucoma treatment.…”
Section: Medical Hypothesis Discovery and Innovation In Optometry Dea...mentioning
confidence: 99%
“…
Medical hypothesis, discovery & innovation in optometry Dear EditorI read with great interest the article by Dr. Mashael Al-Namaeh, entitled "Pharmaceutical treatment of primary open-angle glaucoma. " In this article, the author concentrated on an interesting and remarkable area in POAG treatment [1]; however, a few issues may be worth considering regarding race and its role in glaucoma treatment.Substantial disparities exist in the quality and quantity of medical care received by those of different races, and the race-based special needs and unique responses to pharmaceutical treatment have been underestimated. Race differences must be considered in the design of cost-effective management policies [2] and clinical guidelines.In a systematic review and meta-analysis, Asefa et al [3] revealed that the total variance in the glaucomatous phenotype (V P ) has two main components: genotypic variance (V G ) and environmental variance (V E ).
…”
mentioning
confidence: 99%
“…Primary open-angle glaucoma (POAG) features a progressive optic neuropathy with loss of ganglion cells, open angles on gonioscopy, and specific visual field defects with or without elevated intraocular pressure (IOP) [4,5]. Approximately 74% of all glaucoma cases are diagnosed as POAG [6].…”
Section: Introductionmentioning
confidence: 99%